POSSIBILITIES OF USE OF PRODUCTS FROM WASTE TYRE RECYCLING IN CONCRETE INDUSTRY - Serdar, Marijana; Baričević, Ana; Bjegović, Dubravka; Lakušić, Stjepan (Journal of Applied Engineering Science, 2014)
Paper presents the effect of products obtained during recycling of waste tyres on properties of concrete. Only by taking into account specific properties of each product obtained by recycling, it is possible to apply them in concrete industry for preparation of concrete products with special properties. Products incorporating waste tyres can then be ecologically, technically and economically competitive alternative to products traditionally used in engineering practice.